Agricultural systems as potential sources of emerging human mycoses caused by Trichoderma: a successful, common phylotype of Trichoderma longibrachiatum in the frontline. Issue 21 (9th December 2019) - Hatvani, Lóránt; Homa, Mónika; Chenthamara, Komal; Cai, Feng; Kocsubé, Sándor; Atanasova, Lea; Mlinaric-Missoni, Emilija; Manikandan, Palanisamy; Revathi, Rajaraman; Dóczi, Ilona; Bogáts, Gábor; Narendran, Venkatapathy; et al.
ABSTRACT: Trichoderma species are abundant in different agricultural habitats, but some representatives of this genus, mainly clade Longibrachiatum members are also emerging as causative agents of various human diseases with even fatal outcome. Strains of these species frequently show resistance to commonly used azole antifungals. Based on previous data it is hypothesized that Trichoderma isolates identified in human infections derive from environmental—including agricultural—origins. We examined Trichoderma longibrachiatum Rifai and Trichoderma bissettii Sandoval-Denis & Guarro strains recovered from four novel cases of human mycoses, along with isolates from previous case reports and different agricultural habitats, using multilocus phylogenetic analysis, BIOLOG Phenotype Microarrays and Etest. Strains attributed to T. bissettii were more abundant in both clinical and agricultural specimens compared to T. longibrachiatum . The majority of the isolates of both taxa could tolerate >256, >32 and >32 μg/ml fluconazole, itraconazole and posaconazole, respectively. None of the obtained results revealed characteristic differences between strains of clinical and agricultural origin, nor between the two taxa, supporting that agricultural environments may be significant sources of infections caused by these emerging human fungal pathogens. Furthermore, based on our findings we propose the re-classification of T. bissettii as T. longibrachiatum f. sp. bissettii . Abstract : Agricultural environments as potential sources of opportunistic Trichoderma infections.